Crystal, magnetic, calorimetric and electronic structure investigation of GdScGe1–xSbx compounds. (9th November 2017) - Guillou, F; Pathak, A K; Hackett, T A; Paudyal, D; Mudryk, Y; Pecharsky, V K
Abstract: Experimental investigations of crystal structure, magnetism and heat capacity of compounds in the pseudoternary GdScGe-GdScSb system combined with density functional theory projections have been employed to clarify the interplay between the crystal structure and magnetism in this series of RTX materials ( R   =  rare-earth, T   =  transition metal and X   =  p-block element). We demonstrate that the CeScSi-type structure adopted by GdScGe and CeFeSi-type structure adopted by GdScSb coexist over a limited range of compositions 0.65 ⩽ x ⩽ 0.9 . Antimony for Ge substitutions in GdScGe result in an anisotropic expansion of the unit cell of the parent that is most pronounced along the c axis. We believe that such expansion acts as the driving force for the instability of the double layer CeScSi-type structure of the parent germanide. Extensive, yet limited Sb substitutions 0 ⩽ x < 0.65 lead to a strong reduction of the Curie temperature compared to the GdScGe parent, but without affecting the saturation magnetization. With a further increase in Sb content, the first compositions showing the presence of the CeFeSi-type structure of the antimonide, x ≈ 0.7, coincide with the appearance of an antiferromagnetic phase. The application of a finite magnetic field reveals a jump in magnetization toward a fully saturated ferromagnetic state. This antiferro–ferromagnetic transformation is not associated with a sizeable latent heat, as confirmed by heat capacity measurements. The electronic structure calculations for x = 0.75 indicate that the key factor in the conversion from the ferromagnetic CeScSi-type to the antiferromagnetic CeFeSi-type structure is the disappearance of the induced magnetic moments on Sc. For the parent antimonide, heat capacity measurements indicate an additional transition below the main antiferromagnetic transition.